2014
DOI: 10.1075/lv.14.2.04mar
|View full text |Cite
|
Sign up to set email alerts
|

A typology of Bantu subject inversion

Abstract: This study charts variation in subject inversion constructions in Bantu languages. It distinguishes between seven types of inversion constructions: formal locative inversion, semantic locative inversion, instrument inversion, patient inversion, (clausal) complement inversion, default agreement inversion and agreeing inversion. Based on a set of nine surface variables, a matrix of inversion constructions is developed which identifies characteristics of the set of constructions overall as well as of each individ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
50
0
10

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 77 publications
1
50
0
10
Order By: Relevance
“…It is a complex phenomenon involving phonology (phrasing), morphology (conjoint/disjoint form of the verb), syntax (order of elements), and information structure. Studies carried out on subject inversion in the Bantu language family have shown how the different constructions appear across the family, but also how closely related languages can differ in this domain, making it an interesting candidate for a micro-variation project (Marten and van der Wal 2014).…”
Section: Subject Inversion In a Micro-variation Projectmentioning
confidence: 99%
See 4 more Smart Citations
“…It is a complex phenomenon involving phonology (phrasing), morphology (conjoint/disjoint form of the verb), syntax (order of elements), and information structure. Studies carried out on subject inversion in the Bantu language family have shown how the different constructions appear across the family, but also how closely related languages can differ in this domain, making it an interesting candidate for a micro-variation project (Marten and van der Wal 2014).…”
Section: Subject Inversion In a Micro-variation Projectmentioning
confidence: 99%
“…This has been extensively studied in Bantu linguistics, both for individual languages and comparatively (e.g. Bresnan and Kanerva 1989;Demuth 1990;Demuth and Mmusi 1997;Marten 2006;Zerbian 2006;Buell 2007;Marten 2011;Creissels 2011;Zeller 2013;Marten and van der Wal 2014). The core inversion constructions are recognised through certain diagnostics, to be presented in section 3.3, and have in common that the post-verbal subject is non-topical.…”
Section: Inverted Subjectsmentioning
confidence: 99%
See 3 more Smart Citations